Management accounting practices in Malaysian public universities / Corina Joseph - Corina, Joseph (Universiti Teknologi MARA, Sarawak, 2003)
This study reports on a survey of management accounting practices in public universities in Malaysia. It aims to identify the management accounting practices adopted in the Malaysian public universities and is conducted using the questionnaire survey method.